Cutaneous metastasis of pleomorphic liposarcoma to the scalp: an elusive diagnosis. (5th April 2016) - Yu, JiaDe; Sokumbi, Olayemi
Abstract : Liposarcomas are one of the most common sarcomas arising in the extremities of the elderly. Various subtypes of liposarcomas include well‐differentiated liposarcomas, dedifferentiated liposarcomas, myxoid liposarcomas and pleomorphic liposarcomas. Pleomorphic liposarcomas are the rarest subtype and have the highest malignant potential compared with the other subtypes of liposarcomas. Metastases to internal organs are common but cutaneous metastasis is very rare with only few cases in the literature. We present a patient with a known diagnosis of stage IV metastatic liposarcoma who presented to our clinic with a rapidly growing nodule on the scalp. A biopsy showed a high‐grade poorly differentiated spindled cell neoplasm sparing the epidermis with scattered lipoblasts. Immunostaining for S100, SOX10, and MNF‐116 were negative. To further characterize the neoplasm, immunostaining with MDM‐2 was performed and was also found to be negative. The histologic appearance, immunohistochemical staining, and clinical history support a diagnosis of metastatic pleomorphic liposarcoma to the scalp. The diagnosis of pleomorphic liposarcoma is challenging. It is often difficult to differentiate from myxofibrosarcoma or other high‐grade pleomorphic sarcomas based on histology alone. However, the presence of bizarre lipoblasts and negative MDM‐2 staining can be helpful clues to differentiate this neoplasm from histologic mimics.